2022
DOI: 10.1111/rec.13758
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of greater sage‐grouse to natural and assisted recovery of key vegetation types following wildfire: insights from scat

Abstract: Megafires are creating severe conservation problems worldwide for wildlife that have obligate dependencies on plant species that are foundational but fire‐intolerant. Wildfire‐induced loss of native perennials and increases in exotic annual grasses threaten greater sage‐grouse (GRSG, Centrocercus urophasianus) in its sagebrush steppe habitat in western North America. Post‐fire restoration using herbicides, seeding, and planting of native perennials such as sagebrush are common, but there are few assessments of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Therefore, it is likely the reclamation surfaces in our study were not selected by females with chicks because of the lack of a shrub overstory that acts as concealment cover (Thompson et al 2006, Hagen 2011). For example, in a post‐fire landscape, Germino et al (2023) found that sage‐grouse use, as measured by the density of scat, was greater near sagebrush seedling outplantings when compared to burned areas without sagebrush. Mitigating the impacts of energy development through reclamation is a long‐term strategy, and other approaches to mitigation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely the reclamation surfaces in our study were not selected by females with chicks because of the lack of a shrub overstory that acts as concealment cover (Thompson et al 2006, Hagen 2011). For example, in a post‐fire landscape, Germino et al (2023) found that sage‐grouse use, as measured by the density of scat, was greater near sagebrush seedling outplantings when compared to burned areas without sagebrush. Mitigating the impacts of energy development through reclamation is a long‐term strategy, and other approaches to mitigation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, if an action involved restoring habitat for Sage Grouse (Centrocercus urophasianus), the study had to demonstrate that it had a measurable effect on Sage Grouse, not just the vegetation. This is because habitat restoration does not always have a demonstrable positive effect on the target species, even when habitat quality targets are met (Germino et al, 2023). Simulation studies were not included for similar reasons.…”
Section: Screeningmentioning
confidence: 99%
“…Other approaches to estimate species' responses to conservation actions when empirical data are not available also demonstrate shortcomings. For example, predicted population growth rates based on simulated responses to action can overestimate true responses (Olsen et al, 2021), and using proxies such as habitat quality can be misleading if restoring habitat fails to yield meaningful improvements in species abundances (e.g., (Germino et al, 2023;Tattersall et al, 2020).…”
Section: Introductionmentioning
confidence: 99%